Spatial Mapping Based on the Settlement Carrying Capacity Value in Gunungpati District, Semarang City - Pratamaningtyas Anggraini; Nur Hafida Hidayati; Intan Muning Harjanti (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2022)
Abstract: The City Regional Spatial Plan (RTRW) for Semarang City stipulates that Gunungpati District has a role in developing residential cultivation areas with the determination of several protected area types as well as functioning as a strategic environmental carrying capacity area for the city. Based on Semarang City BPBD, 29 landslides occurred between 2016-2021, which damaged houses, facilities, and residential infrastructure. This study aims to produce spatial mapping for residential area designations through the calculation of its carrying capacity so as to obtain the carrying capacity value or classification of the ability of each village area to accommodate the number of residents. This can then be used as one of the basic considerations in determining the development of residential areas in Gunungpati District. This study uses the quantitative method to determine the residential land's carrying capacity through spatial mapping data processing based on geographic information systems (GIS) using scoring, weighting, and overlay techniques. The spatial mapping produces a landslide vulnerability map with vulnerability classifications covering very low (1.468,17 Ha) to very vulnerable (466.53 Ha) classes as well as cultivation function, buffer, and protected areas distribution in Gunungpati District. The final results show that each region can accommodate the population increase of each village in Gunungpati District, with Jatirejo Village scoring the highest in DDPm value (26.9) and Sukorejo Village scoring the lowest (5.7). Keywords: Landslides, carrying capacity, settlement